(untitled) (Rudarsko-geološko-naftni zbornik, 2016)
Building, dimensional and decorative stones from mining and industry are among the significant resources of Iran. Following China and Italy, Iran is in third place of world production, but only has a minor contribution in international trade. One main reason of this problem is negligence regarding the introduction of dependable mines to foreign customers. On the other hand, the frequency of fatal and non-fatal accidents in these mines implies the necessity of more attention to safety parameters. The first stage to attain this aim is identifying the major factors on safety of these mines and ranking the major mines considering these indices. In this paper, a comprehensive model for ranking of mines in the sense of all imposing attributes with an emphasis on safety parameters is presented. In order to validate the model, 19 active mines of the Pyrtak Company in Lorestan province have been used. In this paper, after determining all the parameters of safety in decorative stone mines and weighting these attributes, using AHP-TOPSIS and fuzzy environment, mines have been ranked. After a systematic evaluation of the decorative stone mines, the most appropriate mine is selected.